The Action of Angiocrine Molecules Sourced from Mechanotransduction-Related Endothelial Cell Partially Explain the Successful of Titanium in Osseointegration - Wood, Patricia Fretes [UNESP]; da Costa Fernandes, Célio Junior [UNESP]; de Almeida, Gerson Santos [UNESP]; Suter, Luisa Camilo [UNESP]; de Lima Parra, João Paulo Ruiz Lucio [UNESP]; Bezerra, Fábio José [UNESP]; Zambuzzi, Willian Fernando [UNESP] (MDPI, 2023)
Since Branemark’s findings, titanium-based alloys have been widely used in implantology. However, their success in dental implants is not known when considering the heterogenicity of housing cells surrounding the peri-implant microenvironment. Additionally, they are expected to recapitulate the physiological coupling between endothelial cells and osteoblasts during appositional bone growth during osseointegration. To investigate whether this crosstalk was happening in this context, we considered the mechanotransduction-related endothelial cell signaling underlying laminar shear stress (up to 3 days), and this angiocrine factor-enriched medium was harvested further to use exposing pre-osteoblasts (pOb) for up to 7 days in vitro. Two titanium surfaces were considered, as follows: double acid etching treatment (w_DAE) and machined surfaces (wo_DAE). These surfaces were used to conditionate the cell culture medium as recommended by ISO10993-5:2016, and this titanium-enriched medium was later used to expose ECs. First, our data showed that there is a difference between the surfaces in releasing Ti molecules to the medium, providing very dynamic surfaces, where the w_DAE was around 25% higher (4 ng/mL) in comparison to the wo_DAE (3 ng/mL). Importantly, the ECs took up some of this titanium content for up to 3 days in culture. However, when this conditioned medium was used to expose pOb for up to 7 days, considering the angiocrine factors released from ECs, the concentration of Ti was lesser than previously reported, reaching around 1 ng/mL and 2 ng/mL, respectively. Thereafter, pOb exposed to this angiocrine factor-enriched medium presented a significant difference when considering the mechanosignaling subjected to the ECs. Shear-stressed ECs showed adequate crosstalk with osteoblasts, stimulating the higher expression of the Runx2 gene and driving higher expressions of Alkaline phosphatase (ALP), bone sialoprotein (BSP), and osteocalcin. Mechanotransduction-related endothelial cell signaling as a source of angiocrine molecules also stimulated the higher expression of the Col3A1 gene in osteoblasts, which suggests it is a relevant protagonist during trabecular bone growth. In fact, we investigated ECM remodeling by first evaluating the expression of genes related to it, and our data showed a higher expression of matrix metalloproteinase (MMP) 2 and MMP9 in response to mechanosignaling-based angiocrine molecules, independent of considering w_DAE or the wo_DAE, and this profile reflected on the MMP2 and MMP9 activities evaluated via gelatin-based zymography. Complimentarily, the ECM remodeling seemed to be a very regulated mechanism in mature osteoblasts during the mineralization process once both TIMP metallopeptidase inhibitor 1 and 2 (TIMP1 and TIMP2, respectively) genes were significantly higher in response to mechanotransduction-related endothelial cell signaling as a source of angiocrine molecules. Altogether, our data show the relevance of mechanosignaling in favoring ECs’ release of bioactive factors peri-implant, which is responsible for creating an osteogenic microenvironment able to drive osteoblast differentiation and modulate ECM remodeling. Taking this into account, it seems that mechanotransduction-based angiocrine molecules explain the successful use of titanium during osseointegration.
Keywords: angiogenesis; endothelial cells; mechanotransduction; osseointegration; osteoblasts; osteogenesis; titanium